Reaction of the pigment system woody plants for gas and dust pollution - Golovatyi, Sergei; Samusik, Elena (Journal of the Belarusian State University. Ecology, 2023)
The article presents the results of assessing the functional state of woody plants growing in the zone of influence of an enterprise for the production of building materials. It has been shown that gas and dust emissions from the enterprise for the production of building materials (JSC Krasnoselskstroymaterialy) cause a restructuring of the functioning of the photosynthetic apparatus of woody plants. It has been established that the deposition of gas and dust substances on the surface of the leaf apparatus of woody plants leads to multidirectional changes in the functioning of the pigment system (chlorophyll a and b, carotenoids) of plants. The studies found a significant decrease in the ratio of chlorophylls a + b / carotenoids within a radius of 1 km from the source of pollution in the leaves of silver birch by 51–68,6 % and at a distance of 6.5 km in the northeast direction – by 48.2 %. For Scots pine, the opposite direction was noted: an increase in the ratio of chlorophylls a + b / carotenoids within a radius of 1 km from the source of pollution in a southeast direction by 21.1 %, and also at a distance of 1 and 6.5 km in a northeast direction by 28.5−29.5 %. It was revealed that the prevailing wind direction has a significant impact only on the activity of the photosynthetic system of Scots pine. At the same time, the degree of influence on the content of chlorophyll a was 28.9 %, on the content of chlorophyll b – 26.8 %; for the content of carotenoids – 29.4 %. A high degree of change in the ratio of chlorophylls a + b / carotenoids can be a diagnostic sign of the resistance of woody plants to technogenic impacts.